Long face syndrome - Ghouniem, Asma Ahmed (faculty of Basic Medical Science - Libyan International Medical University, 2018)
Long face syndrome , also referred to as skeletal open bite , is a relatively common condition characterized by excessive vertical facial development, the aim of this report is to discuss the etiology and characterstic feature of Adenoid Facie
In 1872, C.V Tomes coined the term “Adenoid Facie” or “long Face Syndrome” to describe the dentofacial changes associated with chronic nasal airway obstruction . This syndrome is characterized by gummy smile , high arched palate ,steep mandibular plane ,malocclusion, anterior marginal gingivitis and a narrow nasal vault .